How Cultural Intelligence Develop Students’ Social Entrepreneurship in Indonesia? - Rudi Yacub; Herlina Herlina; Irfan Sophan Himawan (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractThis study aims to identify the ability of cultural intelligence, intellectual capital, and risk perception of students in the formation and development of social entrepreneurship. Students are expected to be able to help solve social problems following the goals of social entrepreneurship. This study uses a deductive approach and quantitative data processing using the Structural Equation Model (SEM). The sample consists of 612 respondents who are students from 11 universities in Indonesia who have taken entrepreneurship courses. The results show that cultural intelligence and intellectual capital had a positive effect on social entrepreneurship, while risk perception did not have a positive effect. This is because students prioritize the formation and development of social entrepreneurship rather than think about the shareable risks. Furthermore, this research contributes to universities and the government in developing social entrepreneurship in the community. Keywords: Cultural Intelligence, Intellectual Capital, Risk Perception, Social Entrepreneurship Bagaimana Kecerdasan Budaya Mengembangkan Kewirausahaan Sosial Mahasiswa di Indonesia? AbstrakPenelitian ini bertujuan untuk mengidentifikasi kemampuan kecerdasan budaya, modal intelektual, dan persepsi risiko mahasiswa dalam pembentukan dan pengembangan kewirausahaan sosial. Mahasiswa diharapkan dapat membantu memecahkan masalah sosial sesuai dengan tujuan kewirausahaan sosial. Penelitian ini menggunakan pendekatan deduktif dan pengolahan data kuantitatif menggunakan Structural Equation Model (SEM). Sampel terdiri dari 612 responden yang merupakan mahasiswa dari 11 perguruan tinggi di Indonesia yang telah mengambil mata kuliah kewirausahaan. Hasil penelitian menunjukkan bahwa kecerdasan budaya dan modal intelektual berpengaruh positif terhadap kewirausahaan sosial, sedangkan persepsi risiko tidak berpengaruh positif. Hal ini dikarenakan mahasiswa lebih mengutamakan pembentukan dan pengembangan social entrepreneurship daripada memikirkan resiko yang dapat ditanggung bersama. Lebih lanjut, penelitian ini memberikan kontribusi bagi perguruan tinggi dan pemerintah dalam mengembangkan kewirausahaan sosial di masyarakat. Kata kunci: Kecerdasan Budaya, Modal Intelektual, Persepsi Risiko, Kewirausahaan Sosial